2020
DOI: 10.1002/ieam.4230
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment and Source Apportionment for Heavy Metals in a Southern Chinese Reservoir Impacted by Stone Mining Activities

Abstract: Metal contaminants in drinking water pose a potential threat to human health. Metal elements (Fe, Mn, Cu, Cr, Cd, As, and Pb) in Shanzi Reservoir, China, a drinking water source for nearby cities, were measured in 2013 and 2014. The distribution characteristics of metal elements in water were identified and a health risk assessment model was used to evaluate potential harm. Principal component analysis and cluster analysis were used to determine the main sources of metal pollutants. The results showed that P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…They may enter the human body directly from drinking water or indirectly via the food chain 4 . The metal contaminants in the water bodies may come from both natural sources (e.g., geological erosion, weathering, precipitation) and anthropogenic activities (e.g., mining, metal processing, industrial wastewater, the application of pesticides and fertilizers) [5][6][7] . In addition, sediments are also a source of metals because metals can be released into overlying water after desorption and then re-suspended in the surface water 8 .…”
mentioning
confidence: 99%
“…They may enter the human body directly from drinking water or indirectly via the food chain 4 . The metal contaminants in the water bodies may come from both natural sources (e.g., geological erosion, weathering, precipitation) and anthropogenic activities (e.g., mining, metal processing, industrial wastewater, the application of pesticides and fertilizers) [5][6][7] . In addition, sediments are also a source of metals because metals can be released into overlying water after desorption and then re-suspended in the surface water 8 .…”
mentioning
confidence: 99%
“…Using polluted wastewater for irrigation, Xiao et al [11] investigated the distribution of heavy metals in the vegetable and paddy crops near an electroplating facility. Zeng et al [12] investigated the distribution of heavy metals and built a model for determining the possible damage to humans. The cancer risk was around 20% higher in the region with hazardous heavy metals in the drinking water than in the rest of the country [13].…”
Section: Introductionmentioning
confidence: 99%
“…There are many sources of metal in water, mainly including nature sources, such as geological erosion, weathering, and precipitation; anthropogenic activities sources, such as mining; metal processing; industrial wastewater; and the application of pesticides and fertilizers [10][11][12]. Many studies have shown that some toxic trace metals have triple effects (carcinogenesis, teratogenesis and mutagenesis).…”
Section: Introductionmentioning
confidence: 99%